The structure of knowledge and the curriculum : essays - Conference on the Structure of Knowledge and the Curriculum( 1963 : San Jose State College); Schwab, Joseph J.; Ford, G. W.; Pugno, Lawrence; State College, San Jose, California (Chicago : Rand McNally, 1964)
44